Colloidal surface interactions and membrane fouling: Investigations at pore scale - Bacchin, P.; Marty, A.; Duru, P.; Meireles, M.; Aimar, P. (Advances in colloid and interface science, 2011)
In this paper, we examine the contributions of colloidal surface interaction in filtration processes. In a first part, we describe the way surface interactions affect the transport of colloidal particles or macromolecules towards a membrane, and its theoretical description. The concept of critical flux is introduced and linked to particle–membrane wall and particle–particle surface interactions. From this review, it seems important to consider how surface interactions occur at pore scale and control the development of fouling layers. In this context, we report in a second part experiments where the capture of micron-sized particles is observed in a poly-dimethylsiloxane (PDMS) microfluidic filtration device. Direct observations of the filtering part by video-microscopy allow to investigate the way the fouling of the microchannels by the particles is taking place. The experimental results underline the important role played by the particle–wall interactions on the way particles are captured during filtration. A small change in surface properties of the PDMS has important consequences in the way pore clogging occurs: in more hydrophobic conditions the particles first form arches at the microchannels entrance, then leading to the growth of a filtration cake, whereas in more hydrophilic conditions the particles are captured on the walls between the microchannels, then leading to the progressive formation of dendrites. To conclude, both experimental and theoretical approaches show the important role played by surface interactions in filtration processes. The complex interplay between multi-body surface interactions and hydrodynamics at nanometric scale leads to clogging phenomena observed experimentally in microfluidic systems that have not been predicted by numerical simulations. In the future, the two way coupling between simulation and experimental approaches at the pore scale have to progress in order to reach a full understanding of the contribution of colloid science in membrane processes.